Autodesk® Revit® 2020 architecture - Hamad, Munir M. (Mercury Learning & Information, 2019)
This is the most comprehensive book you will find on Autodesk Revit 2020 Architecture. Covering all of the 2D concepts, it uses both metric and imperial units to illustrate the myriad drawing and editing tools for this popular application. Use the companion files to set up drawing exercises and projects and see all of the book's figures in color. Revit Architecture 2020 includes over 50 exercises or "mini-workshops," that complete small projects from concept through actual plotting. Solving all of the workshops will simulate the creation of three projects (architectural and mechanical) from beginning to end, without overlooking any of the basic commands and functions in Autodesk Revit Architecture 2020. Features: Covers Autodesk Revit 2020 updates and new features Designed for novice users of Revit 2020 Architecture. Most useful for "teach yourself" or instructor-led Revit training. No previous CAD experience is required Uses both English and metric units in examples, exercises, projects, and descriptions Accompanied by companion files that feature drawings, practice and finished plots, figures, etc. Includes over 50 "mini-workshops" and hundreds of figures that complete small projects Helps you to prepare for the Revit Architecture Certified Professional exam Exercises and projects included for use as a textbook On the Companion Files: (Files also available for downloading from the publisher by emailing proof of purchase to info@merclearning.com) --Practice Drawing Exercises and Projects (Metric & English) --Finished Plots for Drawing Exercises and Projects --All Images from the Text.